Priorities for Public Sector Research on Food Security and Natural Resources Report Presentation by Frank Place, ICRAF, and Alexandre Meybeck, FAO - Place, Frank; Meybeck, Alexandre (2013)
Priorities for Public Sector Research on Food Security and Natural Resources Report Presentation by Frank Place, ICRAF and Alexandre Meybeck, FAO on April 12, 2013 at the Food Security Futures Conference in Dublin, Ireland.